THU0502 Which is the Clinical Relevance of Ultrasound Examination in the Assessment of Established Juvenile Idiopathic Arthritis?. (9th June 2015) - Biancardi, C.; Borzani, I.; Ravelli, A.; Corona, F.; Filocamo, G.
Abstract : Background: Ultrasound (US) is a powerful tool for the assessment of joint disease in children with juvenile idiopathic arthritis (JIA) and it may provide additional information about disease activity and response to therapy in JIA patients. In 2009, the first composite disease activity score for JIA, named the Juvenile Arthritis Disease Activity Score (JADAS), was published (1). This tool includes the following 4 variables: 1) physician global assessment of overall disease activity (PG); 2) parent/patient global assessment of well being (WB); 3) count of joints with active arthritis; and 4) ESR, normalised to a 0–10 scale. The correlation between US findings and the principal variables of disease activity in JIA remains to be established. Objectives: To evaluate the correlation between US findings and the parent's assessment of pain and WB, the PG and ESR. Methods: Before the study visit, parents of children with JIA were asked to complete the Juvenile Arthritis Multidimensional Assessment Report (JAMAR), which includes a standardized assessment of pain and WB on a 21-numbered circle visual analog scales (VAS), and several other parent centered JIA outcome measures. At study visit, a pediatric rheumatologist, who was unaware of parent's reports, performed a formal joint assessment and scored the PG on 21-numbered circle VAS. After the visit, a pediatric radiologist with almost 10 years of experience in US assessment in JIA, valuated independently the presence of synovial hypertrophy/effusion (gray scale US - GSUS) and Power Doppler (PDUS) in metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joints, knees and ankles, and quantified each US feature on a 0-3 semiquantitative scale. In each patient, the Juvenile Arthritis Disease Activity Score (JADAS) 10 was calculated. The correlations between parent pain and WB, PG and ESR were assessed using Spearman's rank correlation. Correlations were considered high if 0.7, moderate if 0.4–0.7, and low if <0.4 Results: The JAMAR was completed by parents of 28 unselected patients, 17 with persistent oligoarthritis, 4 with extended oligoarthritis, 6 with rheumatoid factor-negative polyarthritis, 1 with systemic arthritis; aged between 5 months and 21 years. The median (range) of JADAS 10 was 13 (0-30.8). The table shows the correlation between US score with the variables considered. Conclusions: The results show, for upper extremities, moderate correlation between US findings and the measures of clinical assessment, and low correlation for knee and ankle, evidencing a major agreement of US with clinical variables in the assessment of disease activity in upper extremities compared with lowers. As expected, the correlation with ESR was overall lower. References: Consolaro A, Ruperto N, Bazso A et al.: Development and validation of a composite disease activity score for juvenile idiopathic arthritis. Arthritis Rheum 2009; 61: 658-66. Disclosure of Interest: None declared